Sharing in Action: The Systemic Concept of the Environment in Aleksandr Bogdanov - Rispoli Giulia (Cultural Science)
This paper discusses the novelty of Aleksandr Bogdanov’s approach, which combines the systemic perspectives employed in his Tektology, the general science of organization (1913–1922). In this work, Bogdanov places particular emphasis on the concept of the environment and situates the process of ‘organization’ in a shared social context. The interaction among social agents, and between them and their contextual surroundings, implies a cybernetic relationship. The environment is, in fact, regarded in terms of both its influence in shaping human living conditions and its plasticity in being transformed by human labour for specific purposes. Likewise, in Tektology, Bogdanov considers not only the social context but also biological and ecological systems that foster an emergent relationship between organisms and their environments. On the one hand, the environment favours biological organisms best adapted to its conditions; on the other hand, the environment is seen as a portion of space (ecosystem) in which populations live and continuously modify the biogeochemical conditions of that system. By referring to biological, ecological and cognitive levels of cybernetic organization, I argue that Bogdanov’s tektological polymorphic idea of the environment embraces different dimensions of the systemic discourse, and can also be useful in understanding the process of knowledge creation underlying the idea of a proletarian culture.